Montreal Cognitive Assessment 5‐minute protocol is accurate in screening for mild cognitive impairment in the rural African population: Neuropsychology: Cognitive and functional assessment in diverse populations. (7th December 2020) - Masika, Golden Mwakibo; Yu, Doris S.F.; Li, Polly W.C.; Wong, Adrian; Lin, Rose S.Y.; Lee, Diana T.F.
Abstract: Background: The prevalence of dementia in Tanzania, as in other developing countries is progressively increasing. 1 Yet the screening instruments for the pre‐clinical stage of the diseases are lacking. This study examined the diagnostic accuracy of the Montreal Cognitive Assessment‐5‐minutes protocol (MoCA‐5‐min) among older adult in the rural Tanzania. Methods: After cultural adaptation following Brislin's approach, 2 the MoCA‐5‐min and the IDEA cognitive screening were concurrently administered to community‐dwelling older adults (n=202) in Chamwino district and 40 re‐evaluated at 6 weeks. Exploratory factor analysis (EFA) using principal component method and oblique rotation was performed to determine the underlying factor structure of the scale. The concurrent and the diagnostic accuracy of the MoCA‐5‐min were examined by comparing its score with IDEA cognitive screening and the psychiatrist's diagnosis using DSM‐V criteria respectively. Results: The EFA found that all the MoCA‐5‐min items highly loaded into one component, with factor loading ranging from 0.550 to 0.879. The intraclass correlation coefficient for 6 weeks test‐retest reliability was 0.85. Its strong significant correlation with the IDEA screening (Pearson's r = 0.614, p < 0.001) demonstrated a good concurrent validity. Using the psychiatrist's rating as a gold standard, the area under the curve (AUC) was 0.861, (95% CI = 0.799 – 0.922) (Figure 1). With the optimal cut‐off score for MCI at 22, the sensitivity was 80% and specificity was 74%. As for dementia, at a score of 16 the sensitivity was 90% and specificity was 80%, whereas the AUC was 0.910, (95%CI = 0.852 – 0.967) (Figure 2). Upon stratifying the sample into different age groups, the optimal cut‐off scores tended to decrease with the increase in age (Table 1). Conclusion: The MoCA‐5‐min is reliable and provides a valid and accurate measure of cognitive decline among older population in the rural settings of Tanzania. The use of varying cut‐off scores across age groups may ensure a more precise discriminatory power of the MoCA‐5‐min. References: 1. WHO. Dementia: Key facts [Internet]. World Health Organization ‐ Fact Sheets. 2019 [cited 2019 Nov 11]. p. 1–5. Available from: https://www.who.int/news‐room/fact‐sheets/detail/dementia . 2. Brislin RW. Back‐translation for cross‐cultural research. J Crosss Cult Psychol. 1970;1(3):185–216.